HUBUNGAN ANTARA DUKUNGAN SOSIAL DENGAN RESILIENSI AKADEMIK PADA MAHASISWA TINGKAT AKHIR YANG SEDANG MENYUSUN SKRIPSI DI MEDAN - Tri Novianti Ulindah Simatupang; Hotpascaman Simbolon (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2026)
ABSTRACT The completion of an undergraduate thesis often becomes a challenging academic transition, as students are required to cope with research demands, time constraints, and uncertainties throughout the final stage of their studies. In this situation, social support is considered a psychological resource that may help students maintain their academic adaptability. This study examines the relationship between social support and academic resilience among final-year students who are preparing their undergraduate theses in Medan City. A quantitative approach with a correlational design was employed involving 169 active university students from various higher education institutions selected through purposive sampling. Data were collected online using the Social Support Scale based on Sarafino and Smith’s theory and the Academic Resilience Scale adapted from Cassidy’s instrument. The relationship between variables was analyzed using Spearman’s rho correlation test. The findings revealed a positive and significant relationship between social support and academic resilience (r = 0.616; p = 0.000). This finding indicates that students who perceive higher levels of social support tend to demonstrate stronger academic resilience in dealing with various challenges during the thesis completion process. Social support serves as an important element in strengthening academic resilience; therefore, universities need to develop supportive academic and social environments that enhance students’ psychological readiness to successfully complete their studies. ABSTRAK Penyelesaian skripsi sering menjadi periode transisi akademik yang penuh tuntutan karena mahasiswa perlu menghadapi tekanan penyelesaian penelitian, keterbatasan waktu, serta ketidakpastian selama proses akhir studi. Dalam kondisi tersebut, keberadaan dukungan sosial dipandang sebagai salah satu sumber daya psikologis yang dapat membantu mahasiswa mempertahankan kemampuan adaptasi akademiknya. Penelitian ini mengkaji hubungan antara dukungan sosial dan resiliensi akademik pada mahasiswa tingkat akhir yang sedang menyusun skripsi di Kota Medan. Pendekatan kuantitatif dengan desain korelasional diterapkan pada 169 mahasiswa aktif dari berbagai perguruan tinggi yang dipilih melalui teknik purposive sampling. Data dikumpulkan secara daring menggunakan Skala Dukungan Sosial berdasarkan teori Sarafino dan Smith serta Skala Resiliensi Akademik yang mengacu pada instrumen Cassidy. Pengujian hubungan antarvariabel dilakukan menggunakan korelasi Spearman rho. Hasil analisis menunjukkan adanya hubungan positif dan signifikan antara dukungan sosial dan resiliensi akademik (r = 0,616; p = 0,000). Temuan ini menunjukkan bahwa semakin baik dukungan sosial yang dirasakan mahasiswa, semakin kuat pula kemampuan mereka dalam menghadapi berbagai tantangan akademik selama penyusunan skripsi. Dukungan sosial menjadi elemen penting dalam membangun ketahanan akademik, sehingga perguruan tinggi perlu mengembangkan lingkungan pendampingan yang mampu memperkuat kesiapan psikologis mahasiswa dalam menyelesaikan studi.